Dispossession in the realm of social reproduction in Caaguazú and Itapúa, Paraguay: (Journal on studies and research of academic knowledge, 2022)
This study examines the experiences of peasant and Indigenous women in relation to land access, changing environmental conditions, and reproductive capacities in contemporary Paraguay. Drawing analysis from two communities – one in Caaguazú and the other in Itapúa – the study shows that there are multiple temporalities to land dispossession at work with multiple gendered manifestations of the social reproduction of rural households. The findings demonstrate that the depletion of social reproductive capacities is part of a matrix that facilitates the slow displacement, even as people are responding creatively to rapidly changing conditions. The investigation utilizes a qualitative method, with a particular focus on a multi-sited ethnographic approach. The results illustrate that peasant and Indigenous women are articulating changing conditions of social reproduction along three axes: proximity to agrochemicals changing health outcomes, changing environmental conditions impacting food procurement strategies, and migration circuits altering care infrastructures.
Keywords: Gender; Social reproduction; Peasantry